Reliability-based maintenance (RMC) and its role in improving the availability of production machines - an applied analytical study in the sewing department/ready-made garments factory in Najaf Al-Ashraf - ليث علي الحكيم; الهام ناظم الشيباني; عمار عبد الامير (Iraqi Journal for Administrative Sciences, 2024)
This study sought to determine the role of Reliability-Centered Maintenance (RCM) Availability in improving the availability of production machines (an applied study in the sewing department/ready-made garments factory in Najaf Al-Ashraf. With the acceleration of the wheel of technical progress and crossing the limits of the unreasonable, failures of the machines used in The production process is a major source of concern in the production and operations sectors because of the high technology it possesses, as the failure of any simple part of these machines could have a significant impact on the decrease in reliability and availability, which in turn will be reflected in the production capacity due to a reduction in the amount of production and an increase in operating costs, which It affects the products provided to customers. Perhaps one of the most important treatments offered in this field is the reliability-based maintenance (RCM) approach, as it includes the procedures used to determine the maintenance requirements for any machine within its operating environment. These procedures depend mainly on: 1. What can be done to maintain continuity Operation of production machines. 2. When are maintenance activities carried out on production machines? How can functional failure of production machines be predicted and prevented? . The costs of performing maintenance activities, as these procedures lead to a decrease in potential failures, an increase in reliability, and an improvement in the availability of production machines. In order to achieve the goal of the study, a scientific methodology was developed to determine the nature of the influential relationships between maintenance requirements, increased reliability, and improved availability, and resulted in a set of main hypotheses. And the subcategories that reflect these relationships. The study also relied on a set of indicators and statistical tests, and accordingly, a set of theoretical and field conclusions were indicated, and based on the conclusions reached by the study, a set of recommendations were presented that are consistent with these conclusions.